EFFECT OF ORGANIC AND INORGANIC FERTILIZERS ON YIELD, CHLOROPHYLL CONTENT, DRY MATTER AND KEEPING QUALITY OF POTATO - Kanbi, V H; Bhatnagar, R. (Potato Journal, 2013)
Field experiment was conducted to study the effect of organic-inorganic sources of nitrogen fertilizers on chlorophyll content of leaves (at 65 and 85 days crop), tuber yield, dry matter, chips quality and storage behaviour of potato cv. Kufri Badshah during 2002-03 at Deesa. The application of 25 t/ha organic manure along with 100% recommended dose of nitrogen in inorganic form or more than 50% of recommended dose of nitrogen in inorganic form and remaining parts of nitrogen in castor cake or poultry manure increased the chlorophyll content, tuber yield, tuber dry matter and minimized storage losses and improved quality of chips.